Anatomical study of the leaves and petioles of scab resistant and susceptible apple cultivars - Tóth, M.; Gracza, P. (International Journal of Horticultural Science, 2005)
Anatomic studies have been performed on the leaf blade, petiole and annual shoot on six apple cultivars by means of scanning electron as well as light microscope. Four of the cultivars examined are resistant to scab (Florina, Freedom, MR-10, MR-11), whereas two of them are susceptible (Jonathan and Idared). Preliminary results suggest that differences in the width of cross sections of leaf blades, in hairyness, in the shape and size of epidermal cells, moreover, in the cross sections of petioles and shoots are considerable. Some of the anatomical properties seem to be correlated with scab resistance or susceptility of the respective cultivars. Therefore, further studies extending to other cultivars may corroborate our claims to find causal relations between anatomical traits of the leaves and disease, especially scab resistance of apple cultivars.